2022
DOI: 10.3389/fimmu.2022.948314
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of T cell and atherosclerosis

Abstract: Atherosclerosis (AS) is widespread and develops into circulatory system problems. T cells play an essential regulatory role in AS occurrence and development. So far, there is no bibliometric research on T cells and AS. To learn more about T cell and AS development, 4,381 records were retrieved from Web of Science™ Core Collection. Then, these records were scientometrically analyzed using CiteSpace and VOSviewer in terms of spatiotemporal distribution, author distribution, subject categories, topic distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 95 publications
1
34
0
Order By: Relevance
“…According to the distribution of countries, a majority of the related literature was published by scholars from the United States, China, Germany, and other countries. Similar patterns appeared in bibliometric studies in other areas, such as atherosclerosis 17 and schizophrenia. 18 Inequalities in the distribution of research around the world were revealed, as academic ability depends largely on a country's economic status.…”
Section: Countries and Institutionssupporting
confidence: 78%
“…According to the distribution of countries, a majority of the related literature was published by scholars from the United States, China, Germany, and other countries. Similar patterns appeared in bibliometric studies in other areas, such as atherosclerosis 17 and schizophrenia. 18 Inequalities in the distribution of research around the world were revealed, as academic ability depends largely on a country's economic status.…”
Section: Countries and Institutionssupporting
confidence: 78%
“…Keywords reflect the core theme of the article, rank articles according to the frequency of co-occurrence could facilitate the analysis of the research focus in the field ( 21 ). In this study, we can see that the research focus in this field is mainly on the gut microbiota, inflammation, insulin resistance, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The scientometric analysis is an emerging tool to quickly explore the structure and trends of a topic or domain through statistical methods and visualization ( 10 12 ). It can extract useful information from a large amount of literature by identifying relevant nodes.…”
Section: Introductionmentioning
confidence: 99%